Participatory mapping of climate-related risks in Mekong River Delta - CGIAR Research Program on Climate Change, Agriculture and Food Security (2017)
The infograph shows the steps in the participatory development of flood, drought, and salinity intrusion risk maps, and adaptive cropping systems and cropping calendar for the provinces in the Mekong River Delta.